Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1038/tp.2016.142
|View full text |Cite
|
Sign up to set email alerts
|

Membrane lipidomics in schizophrenia patients: a correlational study with clinical and cognitive manifestations

Abstract: Schizophrenia is a severe mental condition in which several lipid abnormalities—either structural or metabolic—have been described. We tested the hypothesis that an abnormality in membrane lipid composition may contribute to aberrant dopamine signaling, and thereby symptoms and cognitive impairment, in schizophrenia (SCZ) patients. Antipsychotic-medicated and clinically stable SCZ outpatients (n=74) were compared with matched healthy subjects (HC, n=40). A lipidomic analysis was performed in red blood cell (RB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
51
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 64 publications
8
51
0
4
Order By: Relevance
“…Lipid concentration changes were reported for specific lipid classes in many cognitive disorders, including SZ [21][22][23][24][25][26][27]62], ASD [19,20], DS [18], bipolar disorder [26,63], and Alzheimer's disease [64]. In our study, 27 SZ, 17 ASD and five DS patients samples were measured together with the control group in a random order.…”
Section: Lipidome Changes In Cognitive Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipid concentration changes were reported for specific lipid classes in many cognitive disorders, including SZ [21][22][23][24][25][26][27]62], ASD [19,20], DS [18], bipolar disorder [26,63], and Alzheimer's disease [64]. In our study, 27 SZ, 17 ASD and five DS patients samples were measured together with the control group in a random order.…”
Section: Lipidome Changes In Cognitive Disordersmentioning
confidence: 99%
“…These studies, however, focused on specific lipid classes and had limited sample and age representation. Alterations of lipid compositions were reported to be associated with cognitive disorders, including autism (ASD), schizophrenia (SZ), and Down syndrome (DS), by studies examining lipid concentrations in the blood [18][19][20][21][22][23][24][25] and brain [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Study showed changes in the expression of genes associated with sphingolipid metabolism in the prefrontal cortex (Narayan et al, 2009) and skin (Smesny et al, 2013) from schizophrenia patients. In addition, a lipidomic study reported a decrease of SM in red blood cells (RBCs) membranes of schizophrenia patients compared to controls (Tessier et al, 2016). A postmortem study also found decreased SM in brain samples of schizophrenia patients (Schmitt et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Recent lipidomics studies have led to the vast and rapid expansion of the available data on various organs, tissues, cell types, and cell organelles [82,83]. Similarly, data concerning lipidome changes in pathological states, including neurological and mental disorders, provide new insight into the possible role of lipids in neuronal tissues [84][85][86][87][88][89]. Although no direct link has been established so far, it is easy to fathom how an imbalance in the strength of NT-membrane partitioning could contribute to, for example, major depressive disorder or Parkinson's disease.…”
Section: The Effect Of Membrane Lipid Composition On Neurotransmittermentioning
confidence: 99%